2014
DOI: 10.1080/02755947.2014.902411
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of Postrelease Mortality of School‐Size Bluefin Tuna in the U.S. Recreational Troll Fishery

Abstract: The recreational fishery for juvenile Bluefin Tuna Thunnus thynnus along the U.S. Atlantic coast has a large number of regulatory discards, but little information exists on the fate of released fish. We deployed 20 pop‐up satellite archival tags programmed to release after 31 d to estimate the postrelease mortality of school‐size (69–119 cm curved FL) Bluefin Tuna caught in the recreational troll fishery. All fish were captured using lures or lure–bait combinations rigged with standard “J” hooks. Nineteen of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…Studies using pop‐up satellite archival tags have indicated that postrelease mortality of Bluefin Tuna released in recreational fisheries is low (<5%) across size‐classes (Stokesbury et al. ; Marcek and Graves ; Goldsmith et al. ), suggesting that catch‐and‐release angling is a viable conservation strategy that would provide substantial benefits, especially to high‐income anglers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using pop‐up satellite archival tags have indicated that postrelease mortality of Bluefin Tuna released in recreational fisheries is low (<5%) across size‐classes (Stokesbury et al. ; Marcek and Graves ; Goldsmith et al. ), suggesting that catch‐and‐release angling is a viable conservation strategy that would provide substantial benefits, especially to high‐income anglers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the additional value attached by class 1 anglers to nonconsumptive aspects of Bluefin Tuna fishing (catch and release, hooking and losing fish, and other factors captured by the ASC) appear to provide sufficient incentive for this group to continue targeting Bluefin Tuna despite restrictive harvest regulations. Studies using pop-up satellite archival tags have indicated that postrelease mortality of Bluefin Tuna released in recreational fisheries is low (<5%) across size-classes (Stokesbury et al 2011;Marcek and Graves 2014;Goldsmith et al 2017), suggesting that catch-and-release angling is a viable conservation strategy that would provide substantial benefits, especially to high-income anglers.…”
mentioning
confidence: 99%
“…The tag anchor (3.2 cm long × 2.4 cm wide) was a hydroscopic surgicalgrade nylon assembly that was attached to the PSAT with a tether consisting of 16 cm of monofilament fishing line (91-kg breaking strength). A more detailed description of the PSAT assembly and deployment protocol is given by Marcek and Graves (2014).…”
Section: Methodsmentioning
confidence: 99%
“…For scenario 2, a tag's remaining in complete darkness for a certain minimum amount of time was considered an appropriate indicator of predation or scavenging. Ingestion of PSATs (and presumably the fish to which they were attached) by predators or scavengers is well-documented [8,9,18,23], and tags generally remain inside the consumer's stomach for at least several days before being egested, floating to the surface, and transmitting data. Given these findings, tags were programmed to release if maintained in complete darkness for 48 h.…”
Section: Tag Configurationmentioning
confidence: 99%
“…Stokesbury et al [17] deployed PSATs on large medium and giant (≥ 185 cm CFL) Atlantic bluefin tuna captured using bait rigged with barbless circle hooks in an experimental recreational fishery off the coast of Prince Edward Island, Canada, with fight times ranging from 6 to 79 min, and estimated a mortality rate of 3.4% (2 of 59 fish died after release). Marcek and Graves [18] observed a post-release mortality rate of 0% for 19 school-size (91-< 119 cm CFL) Atlantic bluefin tuna tagged with PSATs after being caught using 23-91 kg trolling tackle and fought for 5.5-12 min. Most recently, Tracey et al [19] deployed PSATs on 59 southern bluefin tuna (Thunnus maccoyi), primarily of sizes comparable to the school and large school size classes (91-< 150 cm CFL), caught while trolling artificial lures or drifting with natural baits with 15-37 kg tackle (fight times ranged from 3 to 118 min), estimating a post-release mortality rate of 19%.…”
Section: Introductionmentioning
confidence: 99%